Childhood obesity as a predictor of type 2 diabetes mellitus in adults: a systematic review and meta-analysis - Marco Raditya; Fabiola Cathleen; Daniell Edward Raharjo; Kristian Kurniawan (Indonesian Pediatric Society, 2022)
Background Despite government-developed prevention programs, type 2 diabetes mellitus (DM) has continued to increase, suggesting that the programs are ineffective. Other potential risk factors, such as childhood obesity, may influence adult-onset diabetes. Objective To assess for a potential association between childhood obesity and adult type 2 DM by meta-analysis of the literature. Methods This review was conducted according to the PRISMA Statements' Flow Diagram and Checklist to improve quality of reporting. Cohort studies were chosen for their long-term follow-up. Newcastle-Ottawa Scale for Cohorts (NOS-Cohort) was used to assess for bias and quality of the included studies, in addition to the Cochrane Handbook. Analysis was done with forest and funnel plots using RevMan 5.3 software for Macintosh. Results A total of 237 records with 73,533 participants were retrieved, of which 10 studies were included in our systematic review and 5 studies were included in the meta-analysis. The most common bias based on NOS-Cohort was inadequate follow-up. Forest plot revealed a significant association between childhood obesity and adult diabetes (OR 3.89; 95%CI 2.97-5.09; I2 0%; P<0.00001). Individuals with childhood obesity were 3.89 times more likely to have adult-onset diabetes. Funnel plot assessment was symmetrical. Studies suggested that childhood obesity led to early insulin resistance and adiposity rebound, which promotes adulthood obesity, a diabetic risk factor. Conclusion Childhood obesity can be used as a predictor for adult-onset diabetes. Early diabetes screening and prevention guidelines should include childhood obesity as a plausible risk factor.